Transdermal delivery of botulinum toxin-A through phosphatidylcholine/cholesterol nanoliposomes for treatment of post-acne scarring - Lannan Chen; Lei Cui; Jiabing Ran; Zhengrui Liu; Xiongbin Zhu (Journal of Materials Science: Materials in Medicine)
Abstract As an acne sequela, post-acne scarring (PSA) has huge negative impact on sufferers’ quality of life because of aesthetical embarrassment. Transdermal delivery of botulinum toxin-A (BTXA) is a promising strategy for PAS treatment, but currently reported approaches are far from satisfactory. In this work, phosphatidylcholine/cholesterol (PC/Chol) nanoliposomes were utilized for encapsulation and transdermal delivery of BTXA. The composition, structure, morphology, size, size distribution, etc. of as-prepared BTXA@liposome nanoparticles were investigated in detail. Simulated transdermal delivery assay indicated that the diffusion depth of the BXTA@liposome nanoparticles was nearly 8 times that of pure BTXA and reached 380 μm. 12 facial PSA patients were recruited to evaluate the curative effect of the BTXA@liposome nanoparticles on PSA. Through ECCA (échelle d’évaluation clinique des cicatrices d’acné) scoring and self-evaluation of patients, the resultant data indicated that compared to hyaluronic acid (HA) hydrogel treatment the BTXA@liposome/HA hydrogel treatment could better relieve PSA to some extent but didn’t show significant advantage. Further work is needed to verify the feasibility and curative effect of this method in PSA treatment in the future. Graphical Abstract